SPONTANEOUS EXPULSION OF INTRABRONCHIAL METALLIC FOREIGN BODY: A CASE REPORT - Hadi, Maha A. (Medknow Publications & Media Pvt Ltd, 1997)
Inhalation of metallic foreign bodies is a rare event occurring mostly in children, and often requires early surgical intervention to avoid complications. We report a case of spontaneous expectoration of an intrabronchial metallic nail in an adult, 2 hours after inhalation.